Demarcation of Pollution-Prone Areas around the Manyoni Uranium Project, Tanzania - Farida Lolila; Mohamed S. Mazunga; Ntombizikhona B. Ndabeni (Aerosol and Air Quality Research)
Abstract This study employed PM10 source parameters and pre-processed topographical and meteorological data as input into the AERMOD atmospheric dispersion model to demarcate pollution-prone areas around the Manyoni Uranium Project. Knowing these areas before mining is an important step toward establishing efficient and effective environmental baseline data. This is because resources for collecting the data will be concentrated in areas with higher contamination potential. In this regard, AERMOD predicted that the regions suitable for pollution demarcation would be 25.55 km2, 25.85 km2, and 27.96 km2 if the prospective mine at Playa C1 operated for 5, 7, and 10 years, respectively. Within the demarcated areas, AERMOD predicted that the maximum annual ground level concentration of PM10 averaged over 5, 7, and 10 years would be 22.2 µg m−3, 22.8 µg m−3, and 25.7 µg m−3, respectively. These values are 11%, 14%, and 28.5% higher than the WHO annual limit of 20 µg m−3 for PM10. This information can help mine owners and government agencies figure out ways to protect people and the environment from the expected pollution.